Ortho-Directed Palladium-Catalyzed Direct C–H Functionalization of 3-Picolinyl- and 3-(2-Cyanoethyl)pyrimidin-4(3H)-ones with Aryl Halides - Ruiz, Sandra Collado; Muselli, Mickaël; Frippiat, Steven; Diallo, Thierno Mamoudou; Mohamed-Cherif, Anissa; Levacher, Vincent; Baudequin, Christine; Bischoff, Laurent; Hoarau, Christophe (Synlett, 2020)
The ortho-directed palladium-catalyzed direct C–H arylation of 3-picolinylpyrimidin-4-one was achieved by using various aryl halides. The method was extended to C–H arylation of pyrimidin-4-ones containing a methoxy group and an aryl group at the C5 site. The 2-cyanoethyl substituent was also evaluated as an ortho-directing group. The method gives access to novel N-substituted 2-aryl or 2,5-diaryl pyrimidin-4-ones. A standard three-step deprotection sequence for the picolinyl group was also studied.
Keywords: palladium catalysis; arylation; C–H functionalization; Suzuki coupling; pyrimidinones